A stable nanoscaled Zr-MOF for the detection of toxic mycotoxin through a pH-modulated ratiometric luminescent switch. Issue 40 (14th April 2020) - Guo, Xiaolei; Zhu, Nansong; Lou, Yue; Ren, Siyuan; Pang, Shirui; He, Yiqiang; Chen, Xiao-Bo; Shi, Zhan; Feng, Shouhua
Abstract : A stable nanoscaled single-excitation ratiometric luminescent pH sensor (MPDB-PCN ) for highly sensitive real-time detection of toxic mycotoxin (3-NPA) in complicated environments. Abstract : A stable nanoscaled single-excitation ratiometric luminescent pH sensor (MPDB-PCN ) over a broad pH range from 2.5 to 8.6 is fabricated through post-synthetic modification of PCN-224 with naphthalimide-derived molecules. Due to the rapid, sensitive and linear response to pH, MPDB-PCN is capable of detecting 3-nitropropionic acid (3-NPA), an acid neurotoxin in food safety, with a low detection limit of 15 μM in sugarcane juice.